Information System Use–Related Activity: An Expanded Behavioral Conceptualization of Individual-Level Information System Use - Barki, Henri; Titah, Ryad; Boffo, Céline (Information Systems Research, 2007)
Despite calls for improving current approaches to conceptualizing and measuring the construct of information system use, theoretical advances in this regard are still insufficient. The present paper proposes to expand the focus of existing conceptualizations that exclusively focus on technology interaction behaviors via the construct of IS use-related activity. Based on task-technology fit and activity theory, IS use-related activity is conceptualized as a second-order aggregate construct that comprises both technology interaction behaviors, as well as activities users undertake to adapt the task-technology-individual system. A multiple-indicators and multiple-causes analysis of data collected from 190 users in 21 organizations is found to support the proposed conceptualization.